The Role Of Small Hand Tractors In Increasing Rice Productivity In Enrekang Regency, South Sulawesi - Hasrul Sudirman; Irmayani, Irmayani; Muh Ikbal Putera (International Journal of Economics, Business and Innovation Research, 2024)
Agricultural development requires dynamic agriculture or agriculture that incorporates new technologies. The development of technology can take the form of methods, changes in crop types, changes in inputs, as well as changes in the agricultural tools used in the agricultural production process. The sources of data used are primary data and secondary data. The data collection methods used are observation, interviews, and documentation with a sample size of 10 people. The data analysis method employed is descriptive data analysis techniques. The results of this study indicate that based on the Likert scale test on the utilization of small hand tractor mechanization in agriculture, with an average score of 94.2%, this shows it is very beneficial for farmers in Sanglepongan Village. The role of mechanization tools such as hand tractors in the agricultural cultivation process in Sanglepongan village demonstrates that they are very important and bring various significant benefits to farmers and the agricultural community. Here are some key roles of small hand tractors in agriculture in Sanglepongan Village, namely in land preparation, reducing physical workload, increasing crop productivity, saving time and costs, modernizing agriculture, reducing dependence on labor, and facing weather and seasonal challenges. The impact of using small hand tractors on increasing farmers' production in Sanglepongan village shows that this positive effect is evident not only in the increase in the quantity of harvests but also in the improvement of quality and sustainability of farming practices, timely planting, and a reduction in manual labor.